2023
DOI: 10.1186/s12889-023-16546-2
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality during the Coronavirus disease pandemic in Korea

Changwoo Han,
Hoyeon Jang,
Juhwan Oh

Abstract: Background Although the ongoing epidemics of Coronavirus disease 2019 (COVID-19) may have affected the mortality trend of the nation, the national level assessment of excess mortality (changes in overall mortality in the entire population) is still scarce in Korea. Therefore, this study evaluated the excess mortality during the COVID-19 pandemic in Korea using the certified mortality data. Methods Monthly mortality and population data from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Unfortunately causes of death are not yet available in France for the year 2022, but the higher estimated number of excess deaths than that of COVID-19-attributed deaths likely reflects a long-term indirect impact of the pandemic increasing mortality related to modifications of patient management and healthcare system organization. A similar pattern was also reported in Germany[26] and Korea[27], suggesting a similar impact of the pandemic on healthcare systems and mortality not only in France. Further research is needed to better understand the various features contributing to this perturbation of mortality trends.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately causes of death are not yet available in France for the year 2022, but the higher estimated number of excess deaths than that of COVID-19-attributed deaths likely reflects a long-term indirect impact of the pandemic increasing mortality related to modifications of patient management and healthcare system organization. A similar pattern was also reported in Germany[26] and Korea[27], suggesting a similar impact of the pandemic on healthcare systems and mortality not only in France. Further research is needed to better understand the various features contributing to this perturbation of mortality trends.…”
Section: Discussionsupporting
confidence: 85%
“…The reliability of reported deaths varies greatly between countries, locations and hospitals, and over time and it is difficult to frame COVID-19 as the main cause. When compared with the pre-pandemic period, the mortality rate of nearly 8.04% during the pandemic showed an increasing rate, as international statistics and other studies have shown [32][33][34]. There could be many explanations for this, such as aggravated chronic conditions or presentation to a hospital during the complication phase with or without COVID-19 infection.…”
Section: Discussionmentioning
confidence: 95%
“…While several studies have been conducted 6,7,9 , data on the long-term mortality of COVID-19 survivors, particularly among older adults, and the associated risk factors remain scarce. In Korea, the mortality rate from COVID-19 was relatively low, attributed to stringent quarantine measures 10 , but the older demographic experienced an increase in excess mortality during the pandemic 11 . Therefore, this study aimed to investigate the 1-year mortality rate and associated risk factors among older survivors of COVID-19.…”
Section: Introductionmentioning
confidence: 99%